ANALYSIS OF GROWTH RATIO, INDEPENDENCE AND REGIONAL FINANCIAL EFFECTIVENESS IN WEST SUMBAWA REGENCY 2019-2021 - Sadaruddin, Sadaruddin; Bakti, Teguh Arya; Maulia, Winda; Iskandar, Siska Rozana; Nadia, Zalwa (Laboratorium Riset Ekonomi, 2022)
The purpose of this study is to analyze the Financial Performance of West Sumbawa Regency so that it can be known how the financial performance of West Sumbawa Regency uses the ratio analysis tool for independence, effectiveness and growth in the Regional Financial Realization Report of West Sumbawa Regency. This research uses Budget Realization data for 2018 to 2018 d 2021. with data analysis using a descriptive quantitative method. The results of this study show an independence ratio of 9.82% which is classified as very low with an instructive pattern. The effectiveness ratio of PAD for West Sumbawa district in 2018-2021 with an achievement of 133.02%, from the set budget which is classified as very effective, and the growth ratio in the period 3 years 2019 to 2021 experienced growth but in 2018 PAD growth experienced a drastic decrease of -61.07%.